Trade policy uncertainty and corporate financialization: strategic implications for non-financial firms in China - Wang, Mingyao; Mohd Nor, Normaziah; Abdul Rahim, Norhuda; Khan, Faisal; Zhou, Ziyu (Cogent OA, 2025)
This study investigates the impact of trade policy uncertainty (TPU) on the financialization of non-financial firms in China. Corporate financialization is the process in which corporations prioritize financial assets and generate profits primarily via financial investments rather than product markets. Using 27,339 firm-year observations of China A-share listed companies from unbalanced panel data spanning from 2011-Q1 to 2020-Q4, we utilized the fixed effect model (FEM), instrumental variables–two-stage least squares (IV-2SLS), and generalized method of moments (GMM) approaches. The findings reveal a positive relationship between TPU and corporate financialization. Financing constraints and risk-taking play moderating roles in shaping this relationship. Notably, as TPU rises, companies tend to avoid increasing investment in derivatives. Instead, they expand their precautionary savings by retaining larger amounts of cash. This analysis emphasizes the significance of legislators in ensuring policy stability and fostering a secure business environment. Furthermore, the robustness of these results was sustained when alternative key variables and methodologies were applied.